Character Education in the Novel Raksasa dari Jogja and Its Implementation Design in Learning - Dafit Exsfarudin; Mukti Widayati; Sukarno Sukarno (2022)
This research purposes at finding the values of the character in the novel â€œRaksasa dari Jogjaâ€ and its design for the implementation of the value of character education in the learning of high school students in class XII. The method used is descriptive qualitative with data in the form of quote words and sentences containing character values with the data source in the form of the novel â€œRaksasa dari Jogjaâ€ by Dwitasari. The results showed that the novel â€œRaksasa dari Jogjaâ€ contains five-character values in the form of religious values (firm stance sincerity); nationalist character values (maintaining the nation's culture, love for the homeland); independence values (courage, fighting power, hard work, resilience, lifelong learning);Â gotong royongÂ values (non-violence help); and integrity values (responsibility and example). Implementation in learning is adjusted to the basic competencies 3.3 and 4.3 for senior high school class XII.